Beliefs About Advanced Cancer Curability in Older Patients, Their Caregivers, and Oncologists. (23rd April 2019) - Loh, Kah Poh; Mohile, Supriya G.; Lund, Jennifer L.; Epstein, Ronald; Lei, Lianlian; Culakova, Eva; McHugh, Colin; Wells, Megan; Gilmore, Nikesha; Mohamed, Mostafa R.; Kamen, Charles; Aarne, Valerie; et al.
Abstract: Background: Ensuring older patients with advanced cancer and their oncologists have similar beliefs about curability is important. We investigated discordance in beliefs about curability in patient‐oncologist and caregiver‐oncologist dyads. Materials and Methods: We used baseline data from a cluster randomized trial assessing whether geriatric assessment improves communication and quality of life in older patients with advanced cancer and their caregivers. Patients were aged ≥70 years with incurable cancer from community oncology practices. Patients, caregivers, and oncologists were asked: "What do you believe are the chances the cancer will go away and never come back with treatment?" Options were 100%, >50%, 50/50, <50%, and 0% (5‐point scale). Discordance in beliefs about curability was defined as any difference in scale scores (≥3 points were severe). We used multivariate logistic regressions to describe correlates of discordance. Results: Discordance was present in 60% (15% severe) of the 336 patient‐oncologist dyads and 52% (16% severe) of the 245 caregiver‐oncologist dyads. Discordance was less common in patient‐oncologist dyads when oncologists practiced longer (adjusted odds ratio [AOR] 0.90, 95% confidence interval [CI] 0.84–0.97) and more common in non‐Hispanic white patients (AOR 5.77, CI 1.90–17.50) and when patients had lung (AOR 1.95, CI 1.29–2.94) or gastrointestinal (AOR 1.55, CI 1.09–2.21) compared with breast cancer. Severe discordance was more common when patients were non‐Hispanic white, had lower income, and had impaired social support. Caregiver‐oncologist discordance was more common when caregivers were non‐Hispanic white (AOR 3.32, CI 1.01–10.94) and reported lower physical health (AOR 0.88, CI 0.78–1.00). Severe discordance was more common when caregivers had lower income and lower anxiety level. Conclusion: Discordance in beliefs about curability is common, occasionally severe, and correlated with patient, caregiver, and oncologist characteristics. Abstract : Beliefs about cancer curability and estimated survival can differ between patients with cancer and their oncologists, which can affect treatment decision making. This article addresses discordance in beliefs between older patients and their oncologists, as well as between caregivers and oncologists.